2017
DOI: 10.1155/2017/5046076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Distance between Nanoparticles in Clusters on the Magnetization Reversal Process

Abstract: Fourfold magnetic nanoparticles, created from nanowires or in the form of an open square, offer the possibility of creating quaternary memory devices with four unambiguously distinguishable stable states at remanence. This feature, however, has been simulated for single magnetic nanoparticles or clusters with interparticle distances similar to the nanoparticle dimensions. For the possible use in bit-patterned media, it is important to understand the scaling behavior of the stability of the additional intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, a cation reordering was reported to occur in magnetite above 427 • C, corresponding to a gradual transformation from disordered to partially ordered configuration of magnetite [84]. These structural and magnetic effects may also have influenced the hysteresis loop shapes, in addition to the strong mass and volume loss; the latter resulting from an overproportioned shortening of the fibers as compared to the diameter increase, depicted in Figures 4 and 5, of the fibers during stabilization and carbonization [78][79][80], which automatically reduced the distances between neighboring nanoparticles and thus influenced their collective magnetic characteristics [85]. Figure 8 shows a comparison of nanofiber mats and thin films, prepared from PAN with both magnetic nanoparticles used in this study.…”
Section: Magnetic Investigationsmentioning
confidence: 99%
“…In addition, a cation reordering was reported to occur in magnetite above 427 • C, corresponding to a gradual transformation from disordered to partially ordered configuration of magnetite [84]. These structural and magnetic effects may also have influenced the hysteresis loop shapes, in addition to the strong mass and volume loss; the latter resulting from an overproportioned shortening of the fibers as compared to the diameter increase, depicted in Figures 4 and 5, of the fibers during stabilization and carbonization [78][79][80], which automatically reduced the distances between neighboring nanoparticles and thus influenced their collective magnetic characteristics [85]. Figure 8 shows a comparison of nanofiber mats and thin films, prepared from PAN with both magnetic nanoparticles used in this study.…”
Section: Magnetic Investigationsmentioning
confidence: 99%
“…Our recent simulations concentrate on individual nano-elements, before in a future simulation arrays of these structures will be modeled. Recent simulations of iron nanoparticles revealed that for inter-particle distances similar to the particle diameters, the influence of interactions with neighboring particles is relatively small [38,39], so that simulating individual elements firstly can be expected to be sufficient for a first comparison with the experiment.…”
Section: Methodsmentioning
confidence: 99%